Innovativeness in Norway and the Czech Republic - Skuhrovec, Tomáš (2024)
Norway is one of the most successful countries in the world in terms of innovation and economic development. This thesis examines the various factors that lead to their high quality, primarily by using the Global Innovation Index (GII) and the indicators that form this index. At the same time, the thesis includes a comparison of the Norwegian and Czech economies in terms of innovativeness, leading to implications drawn from Norway's strengths that could be applied to the Czech Republic.